50 years after passing the employment promotion law: The development of German labour market policy as progress or regression? - Dingeldey, Irene (Momentum Quarterly, 2020)
The employment promotion law (Arbeitsförderungsgesetz, AFG) from 1969 is regarded as a particularly advanced blueprint of active labour market policy in Germany. In contrast to past anniversaries appraisals in 2019 were missing – possibly because the AFG had been integrated into the Social Law Codebook III and a paradigm shift from active to activating labour market policy was performed. Nevertheless, we take the AFG as a starting point to answer the question about social progress made in different stages of labour market policy – punctually including reforms of unemployment and social benefits as well as exemplary services in related policy fields. As various international organisations recently published strategy papers on a future-oriented labour market and social policy, we create a benchmark of progress based on common elements there in. The result indicates ambivalences of progress and regress - with reservation to the fact that the indicated changes are not exclusively generated by labour market policy, but often by social and economic change.